Immunogenicity Measures of Influenza Vaccines: A Study of 1164 Registered Clinical Trials - Alexander Domnich; Ilaria Manini; Donatella Panatto; Giovanna Elisa Calabrò; Emanuele Montomoli (Vaccines, 2020)
Influenza carries an enormous burden each year. Annual influenza vaccination is the best means of reducing this burden. To be clinically effective, influenza vaccines must be immunogenic, and several immunological assays to test their immunogenicity have been developed. This study aimed to describe the patterns of use of the various immunological assays available to measure the influenza vaccine-induced adaptive immune response and to determine its correlates of protection. A total of 76.5% of the studies included in our analysis measured only the humoral immune response. Among these, the hemagglutination-inhibition assay was by far the most widely used. Other, less common, humoral immune response assays were: virus neutralization (21.7%), enzyme-linked immunosorbent (10.1%), single radial hemolysis (4.6%), and assays able to quantify anti-neuraminidase antibodies (1.7%). By contrast, cell-mediated immunity was quantified in only 23.5% of studies. Several variables were significantly associated with the use of single assays. Specifically, some influenza vaccine types (e.g., adjuvanted, live attenuated and cell culture-derived or recombinant), study phase and study sponsorship pattern were usually found to be statistically significant predictors. We discuss the principal findings and make some suggestions from the point of view of the various stakeholders.